Giant borderline ovarian tumours – review of the literature - Sadlecki Pawel; Dejewska Katarzyna; Domieracka Patrycja; Walentowicz-Sadlecka Malgorzata (Open Medicine)
Giant borderline ovarian tumours (GBOTs) are rare neoplasms that require meticulous management to prevent high-risk operative complications. The broader goal of this systematic review is to consolidate the existing knowledge on GBOTs by focusing on diagnostic approaches, differential diagnoses, and treatment strategies. Furthermore, the relationship between the clinical features of GBOTs and the types of diagnostic and therapeutic procedures implemented was determined.